Climatic and socioeconomic conditions jointly drive the carbon emissions of the urban passenger transport sector - Siyan Chen; Haiyan Duan; Junhua Song; Zhiyuan Duan; Bailin He; Zhenhui Gao; Lixiao Zhang (Humanities & Social Sciences Communications)
Abstract Because of the dramatic rise in vehicle holdings, 21% of global energy consumption and nearly a quarter of carbon emissions now come from the transportation sector. However, the carbon emissions of the urban passenger transport sector (CEUPT) in provincial regions across different climatic zones and the influence of climate conditions on the CEUPT remain ambiguous. Herein, the CEUPT values of 31 provinces in China are quantified by constructing a “bottom-up” calculation model. Then, we elucidate the mechanisms through which climate and socioeconomic conditions jointly influence CEUPT. China’s CEUPT amounted to 483.7 Mt CO2, with a carbon intensity of 0.108 kgCO2/km in 2019. Private cars and motorcycles are the primary sources of carbon emissions, accounting for 295.8 Mt CO2 (61.2%) and 105.66 Mt CO2 (21.9%), respectively. Climate conditions determine people’s initial choice of travel mode, whereas socioeconomic conditions enable people to choose their preferred mode of travel, leading to spatiotemporal variations in the CEUPT. These findings should serve as references for government departments in regions with diverse climates to more extensively consider climate and socioeconomic conditions when formulating energy-saving policies for the urban passenger transport sector, thereby developing more targeted strategies to control the CEUPT.